Knowledge, Working Mother, Husband’s Support, and Exclusive Breastfeeding in Working Area of Padang Serai Primary Health Care Bengkulu City - Nurul Khairani; Suryani Suryani; S. Effendi; Herly Wulandika (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
The bad impact caused by not giving exclusive breastfeeding is the baby's immune system decreases, disruption of baby's growth and development, increases the risk of disease, and is susceptible to bacteria causing diarrhea. The purpose of the study was to determine the relationship between knowledge, working mothers and husband's support with exclusive breastfeeding in Padang Serai Public Health Center in Bengkulu. This type of research was an analytical survey using Cross Sectional design. The sample in this research was mothers who had babies over the age of 6-12 months in Baruna 3 Posyandu and Baruna 2 Posyandu and the sampling used Accidental Sampling techniques, which were as many as 34 mothers. Data collection used primary data and secondary data. This study used the Chi-Square test (Pearson Chi-Square) and Contingency Cofficient. The results of this research were obtained from 34 mothers, there were 17 mothers (50.0%) with less knowledge, 25 mothers (73.5%) who did not work outside the home, 19 mothers (55.9%) whose husbands not supportive and 26 mothers (76.5%) who did not give exclusive breastfeeding, there was a significant relationship between knowledge of mothers with exclusive breastfeeding, there was no significant relationship between mothers working with exclusive breastfeeding, and no significant relationship between husband's support with exclusive breastfeeding in the working area of Padang Serai Health Center in Bengkulu City. It was expected for mothers who had babies to be able to take part in health promotion activities, read books about ASI, to increase their knowledge of the importance of Exclusive Breastfeeding. Keywords: exclusive breastfeeding, husband’s support, knowledge, working mother